Effect of pellet size and adhesive ratio on the production of kenaf pellet as a fossil fuel - Krishnan, S.; Nasrullah, M.; S., Mohamad (Universiti Malaysia Pahang, 2022)
This research presents an investigation on the pellet size and adhesive ratio towards the production of kenaf pellet. The examined operating parameters were pellet size (2 - 3 cm) and adhesive ratio (0 - 15 wt%). The sample was densified through hot and cold molding press machine at 130 °C and 7 MPa. The analysis of the pellet was done through scanning electron microscope (SEM) analysis, calorific value, and combustion analysis. SEM analysis was used to study the surface morphology of the different starch content in kenaf pellets. The best surface recorded was the pellet with a 2.5 cm diameter at 10 wt% starch ratios as it shows clearly the structure of the starch. Calorific value analysis was recorded and the highest value obtained for the pellet with 15 wt% of starch is 46.2 kJ/kg. The highest mass yield for the pyrolysis process was achieved for the pellet at 15 wt% starch content. Pellet production is useful for fossil fuel in exchange for coal as it is more environmentally friendly and classified as renewable energy. Besides, pellet form can be conveniently used for storage and transportation.